Microglia influence immune responses and restrict neurologic disease in response to central nervous system infection by a neurotropic murine coronavirus - Syage, Amber; Pachow, Collin; Cheng, Yuting; Mangale, Vrushali; Green, Kim N.; Lane, Thomas E. (Frontiers in Cellular Neuroscience, 2023)
inoculation of susceptible mice with a glial-tropic strain of mouse hepatitis virus (JHMV), a murine coronavirus, results in an acute encephalomyelitis followed by viral persistence in white matter tracts accompanied by chronic neuroinflammation and demyelination. Microglia serve numerous functions including maintenance of the healthy central nervous system (CNS) and are among the first responders to injury or infection. More recently, studies have demonstrated that microglia aid in tailoring innate and adaptive immune responses following infection by neurotropic viruses including flaviviruses, herpesviruses, and picornaviruses. These findings have emphasized an important role for microglia in host defense against these viral pathogens. In addition, microglia are also critical in optimizing immune-mediated control of JHMV replication within the CNS while restricting the severity of demyelination and enhancing remyelination. This review will highlight our current understanding of the molecular and cellular mechanisms by which microglia aid in host defense, limit neurologic disease, and promote repair following CNS infection by a neurotropic murine coronavirus.